EDUCAÇÃO EM SAÚDE NO CUIDADO A PESSOAS USUÁRIAS DE DROGAS - Vasconcelos, Selene Cordeiro; Frazão, Iracema da Silva; Nascimento, Vilmar da Silva; Lima, Murilo Duarte da Costa; Ramos, Vânia Pinheiro (Revista Baiana de Enfermagem‏, 2014)
<!--[if gte mso 9]>